2016
DOI: 10.2106/jbjs.16.00093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Reoperation and Complications After Total Knee Arthroplasty

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 36 publications
4
76
1
6
Order By: Relevance
“…Geriatric patients aged over 85 are signi cantly less likely to receive TKA than their younger counterparts; it may be that among patients who do undergo arthroplasty, increased age re ects the selection process of appropriate surgical candidates rather than being a protective factor, as only patients with limited comorbidities who are likely to experience long term bene ts would be considered for total arthroplasty procedures 6 . Increased BMI in THA was the single patient factor that was consistently positively associated with major complications, including infection, reoperation and readmission which is in accordance with previous studies which showed BMI to have strong associations with dislocation, infection and revision 52,53 . A study using the New Zealand Joint Registry also reported an OR of 3.73 for PJI in patients with BMI >40 compared to patients with BMI <35 54 .…”
Section: Patient Characteristics Associated With Complicationssupporting
confidence: 90%
“…Geriatric patients aged over 85 are signi cantly less likely to receive TKA than their younger counterparts; it may be that among patients who do undergo arthroplasty, increased age re ects the selection process of appropriate surgical candidates rather than being a protective factor, as only patients with limited comorbidities who are likely to experience long term bene ts would be considered for total arthroplasty procedures 6 . Increased BMI in THA was the single patient factor that was consistently positively associated with major complications, including infection, reoperation and readmission which is in accordance with previous studies which showed BMI to have strong associations with dislocation, infection and revision 52,53 . A study using the New Zealand Joint Registry also reported an OR of 3.73 for PJI in patients with BMI >40 compared to patients with BMI <35 54 .…”
Section: Patient Characteristics Associated With Complicationssupporting
confidence: 90%
“…However, most of the studies report overall risk for revision without detailing reasons for revision. The effect of obesity on revision besides an increased risk for periprosthetic joint infection (PJI) has not been thoroughly discussed in the literature (D'Apuzzo et al 2015, Wagner et al 2016, Jung et al 2017, Roche et al 2018, Boyce et al 2019. There might be a complex relation between weight and height, and TKA outcome.…”
mentioning
confidence: 99%
“…Future studies may consider comparing readmissions with standardized chemoprophylaxis, greater coordination of pre-and postsurgical care, and strict adherence to patient selection such as better glycemic control or BMI limits. 42,43 Readmissions following elective TKA are difficult to predict and prevent, and may not be a valid means for determining quality of care. Finally, it is possible that these readmission rates reflect the lower limit of what is acceptable in the current arthroplasty landscape.…”
Section: Discussionmentioning
confidence: 99%